Question particles in Basque - Monforte, Sergio (Isogloss, 2019)
This article proposes separate analyses for the question particles -a and al in Basque, which occur only in polarity questions, within the framework of Generative Grammar. I will propose that the former one, used in the eastern dialects, is the head of FiniteP and that the latter one, used in the central dialects, occupies the head of Particle Phrase located between TP and the CP field. I provide the following evidence in support of this dual analysis: 1) -a can be used with ote but no other particle can appear at the same time with al; 2) al is compatible with allocutivity but -a is not; 4) and, finally, al can be used in embedded clauses, whereas -a cannot. The fact that -a is not allowed to occur in indirect questions and that it is incompatible with the allocutive verbal paradigm shows that it is in complementary distribution with the head of CP and, therefore, that -a occupies such a head; on the other hand, the impossibility of al to appear with other particles suggest that they must occur in the same position and, since it can appear in embedded questions and with allocutive forms, it does not occupy the head of the CP, but the head of a phrase below.